Performance Analysis of RIS-Assisted Smart Grid Wide Area Network With RF Energy Harvesting - Kandi Veera Venkata Ramana; Hemanta Kumar Sahu (IEEE Access)
This paper presents a comprehensive performance analysis of a reconfigurable intelligent surface (RIS)-assisted smart grid (SG) communication network with radio-frequency (RF) energy harvesting (EH). Here, we have considered a wide area network (WAN) where the dynamic behaviour of home appliances (HAs) switches between active and doze states. The switching action is modelled using a Markov chain coupled with a Saleh-Valenzuela (S-V) channel. These assumptions enable a detailed evaluation of key system parameters, including the number of active appliances, traffic intensity, power splitting ratio, RIS reflectors, and distances between HAs and the control unit (CU). Our study reveals that the proposed system significantly enhances communication performance compared to conventional SG WANs without RIS or RF EH. Specifically, a notable improvement in average bit error probability (ABEP) is demonstrated, achieving up to 7 dB signal-to-noise (SNR) enhancement over benchmarks under identical conditions. We have derived the closed-form average bit error probability (ABEP) expressions for both RIS with dual-hop (RIS-DH) and RIS as transmitter (RIS-T) cases. The results demonstrate that increasing the number of active appliances, traffic intensity, power splitting ratio, and fading severity impacts overall system performance. The derived analytical results are validated through Monte Carlo simulations. This work highlights the potential of RIS and EH technologies to improve energy efficiency and reliability in future SG networks.